Early Christian Interpretation of the Jewish Scriptures: Precursor to Modern Historical Criticism? - HOLLADAY, Carl R. (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
This essay explores C. F. D. Moule’s intriguing suggestion that early Christian interpretation of Scripture, especially the use of promise-fulfillment and typology as hermeneutical approaches, anticipated some aspects of the modern historical-critical method. Included is a discussion of the metaphorical use of “flat” (two-dimensional) and “round” (three-dimensional) to characterize ways of reading Scripture. Attention is given to two ancient authors—Philo of Alexandria and Ptolemy’s Epistle to Flora—both of whom exemplify three-dimensional approaches to Scripture interpretation, although in different ways.